The changing constitution - Jowell, Jeffrey (Oxford University Press, 2000)
Since its first edition in 1985, The Changing Constitution has cemented its reputation for providing concise, scholarly and thought-provoking essays on the key issues surrounding the UK's constitutional development, and the current debates around reform. The seventh edition of this highly successful volume is published at a time of accelerated constitutional change in the wake of the 2010 general election and the formation of a Conservative / Liberal Democrat coalition committed to political reforms - including fixed term parliaments, a referendum on electoral reform, reform of the House of Lords, improved freedom of information, and reform of the House of Commons. This collection of essays provides thoroughly updated versions of previously-published chapters, plus an introductory overview of how the UK constitution is evolving and new chapters on the regulation of information and on the environment as a case study in regulation. Professors Jowell and Oliver have brought together fifteen expert contributors to offer an invaluable source of material and analysis for all students of constitutional law and politics-- Provided by publisher